A Case of Cutaneous Plasmablastic Lymphoma in HIV/AIDS with Disseminated Cryptococcus. (26th November 2013) - Gong, Jun; Alkan, Serhan; Anand, Sidharth
Abstract : We present a case of a patient with HIV/AIDS who presented with a tender left lower extremity cutaneous mass over a site of previous cryptococcal infection and was found to have plasmablastic lymphoma (PBL). The incidence of PBL is estimated to account for less than 5% of all cases of non-Hodgkin lymphoma (NHL) in HIV-positive individuals. In fact, there were only two reports of extraoral PBL at the time of a 2003 review. PBL in HIV-positive individuals is an aggressive malignancy that tends to occur in middle-aged males with low CD4 counts, high viral loads, and chronic HIV infection. The definitive diagnosis can be made with biopsy which typically shows malignant lymphoid cells that stain positive for plasma cell markers and negative for B-cell markers. The most common treatment is chemotherapy with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) or CHOP-like regimens, but the overall survival rate is poor despite its relative responsiveness to chemotherapy. This case highlights the challenges that remain in improving clinical outcomes, the importance of antiretroviral therapy and HIV disease control, and a potential association between a chronic inflammatory state caused by disseminated Cryptococcus and tumorigenesis in individuals with PBL.